Transcriptomes of an Array of Chicken Ovary, Intestinal, and Immune Cells and Tissues - Overbey, Eliah G.; Ng, Theros T.; Catini, Pietro; Griggs, Lisa M.; Stewart, Paul; Tkalcic, Suzana; Hawkins, R. David; Drechsler, Yvonne (Frontiers in Genetics, 2021)
While the chicken (Gallus gallus) is the most consumed agricultural animal worldwide, the chicken transcriptome remains understudied. We have characterized the transcriptome of 10 cell and tissue types from the chicken using RNA-seq, spanning intestinal tissues (ileum, jejunum, proximal cecum), immune cells (B cells, bursa, macrophages, monocytes, spleen T cells, thymus), and reproductive tissue (ovary). We detected 17,872 genes and 24,812 transcripts across all cell and tissue types, representing 73% and 63% of the current gene annotation, respectively. Further quantification of RNA transcript biotypes revealed protein-coding and lncRNAs specific to an individual cell/tissue type. Each cell/tissue type also has an average of around 1.2 isoforms per gene, however, they all have at least one gene with at least 11 isoforms. Differential expression analysis revealed a large number of differentially expressed genes between tissues of the same category (immune and intestinal). Many of these differentially expressed genes in immune cells were involved in cellular processes relating to differentiation and cell metabolism as well as basic functions of immune cells such as cell adhesion and signal transduction. The differential expressed genes of the different segments of the chicken intestine (jejunum, ileum, proximal cecum) correlated to the metabolic processes in nutrient digestion and absorption. These data should provide a valuable resource in understanding the chicken genome.